Modelling the dynamic behaviour of the truck-crane - Mijailović, Radomir (Transport, 2011)
The paper deals with the problem of a dynamic analysis of truck-cranes. Therefore, the article has developed a mechanical-mathematical model having 18 generalized coordinates. Depending on the type of truck crane operation as well as on the fact whether the aim of the article is to conduct the dynamic analysis of the whole truck crane or only that of one of its components, simpler mechanical models are also offered. The presented model is more realistic than those describing the dynamic behaviour of the truck-crane performing all necessary functions, i.e. a mobile means of lifting, transportation and reloading. First Published Online: 09 Jan 2012